Pengaruh Pemanfaatan Fitur Virtual Try-On Berbasis Augmented Reality Dan Testimoni Konsumen Terhadap Minat Beli Foundation Maybelline Ditinjau Dalam Perspektif Bisnis Islam (Studi Pada Gen Z Di Bandar Lampung) - Kirana, Pasya Nindio; Habibi , Ahmad; Heni Verawati (Universitas Nusa Nipa Maumere, 2026)
This study aims to analyze the effect of Augmented Reality-based Virtual Try-On and consumer testimonials on purchase intention toward Maybelline foundation from an Islamic business perspective among Generation Z in Bandar Lampung. This research employs a quantitative approach using primary data collected through questionnaires distributed to 100 respondents. The data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The results show that Virtual Try-On has a positive and significant effect on purchase intention. Consumer testimonials also have a positive and significant effect on purchase intention. Simultaneously, both variables significantly influence purchase intention. From an Islamic business perspective, the use of technology and consumer testimonials can serve as an effective marketing strategy while maintaining ethical principles such as transparency, honesty, and fairness.